2013
DOI: 10.1002/clen.201200434
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Heavy Metals from Contaminated Soil by Two Amaranthus spp.

Abstract: Two medicinal species of amaranth, Amaranthus viridis L. and A. caudatus L. were evaluated for their ability to uptake heavy metals from a contaminated soil. Twenty healthy plants of each species were transplanted to plastic pots containing the soil contaminated with elevated concentrations of Cd, Cr, Cu, Ni, Pb, and Zn. The plants were harvested after 45 days. Below‐ and above‐ground tissues (roots and shoots) were analyzed separately to determine metals concentrations. Compared with the control group, the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…After studying six leafy vegetables out of which two were Amaranthus lividus L. and Amaranthus gangeticus L., Ahmed et al ( 2022 ) found the lowest Cu concentrations for the two Amaranthus species. Furthermore, soil amendments (e.g., S,S-EDDS) were found especially effective in solubilizing Cu and triggering its translocation into the leaves of A. viridis and A. caudatus (Ko et al 2013 ). We observed this pattern without the use of any substances, indicating the effectiveness of Amaranthus leaves in Cu accumulation based on its inherent ability.…”
Section: Discussionmentioning
confidence: 99%
“…After studying six leafy vegetables out of which two were Amaranthus lividus L. and Amaranthus gangeticus L., Ahmed et al ( 2022 ) found the lowest Cu concentrations for the two Amaranthus species. Furthermore, soil amendments (e.g., S,S-EDDS) were found especially effective in solubilizing Cu and triggering its translocation into the leaves of A. viridis and A. caudatus (Ko et al 2013 ). We observed this pattern without the use of any substances, indicating the effectiveness of Amaranthus leaves in Cu accumulation based on its inherent ability.…”
Section: Discussionmentioning
confidence: 99%
“…Amaranthus species attract a special interest in the context of Zn stress due to their importance as a source for valuable nutrient-rich foods and fodder crops (Achigan-Dako et al, 2014) with pronounced stress tolerance and well-characterized potential for HM phytoremediation (Watanabe et al, 2009;Bosiacki et al, 2013;Ko et al, 2014). From the point of primary metabolism, this genus is featured with C4 type of photosynthesis (Ludwig, 2016) and elevated production of oxalic acid (Gélinas and Seguin, 2007;Osmolovskaya et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…Phytoremediation, the use of plants along with their microbial association for remediation of contaminated soils, is a promising solar‐driven, cost‐effective and environmentally suitable alternative for restoration of PTEs‐contaminated soils . However, most hyperaccumulator plants usually have low biomass and slow growth, which limits their application in large‐scale operations . Furthermore, while the total Pb concentrations are high in many of the contaminated sites, the bioavailable fraction of Pb is often very low in the soil environment, especially in calcareous soils due to complexation with various organic and inorganic soil colloids, sorption on oxides and clays, and precipitation as carbonate minerals .…”
Section: Introductionmentioning
confidence: 99%